2021
DOI: 10.1007/s00464-021-08821-3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying curriculum content for a cross-specialty robotic-assisted surgery training program: a Delphi study

Abstract: This study is part of a Ph.D. project funded by the University of Southern Denmark (Faculty scholarship for Peter Hertz). The funder did not influence the protocol development or had access to the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Zattoni F. et al 5 observed that the assistant surgeon committed the most errors during an emergency simulation and highlighted the necessity to include this member in the training procedures for robotic surgery. Hertz P. et al, 18 in their study of robotic surgery training programs, state that assistant surgeons should be given basic training in robotic surgery before participating in these surgeries, particularly due to their rotation within surgical teams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zattoni F. et al 5 observed that the assistant surgeon committed the most errors during an emergency simulation and highlighted the necessity to include this member in the training procedures for robotic surgery. Hertz P. et al, 18 in their study of robotic surgery training programs, state that assistant surgeons should be given basic training in robotic surgery before participating in these surgeries, particularly due to their rotation within surgical teams.…”
Section: Discussionmentioning
confidence: 99%
“…Zattoni F. et al5 observed that the assistant surgeon committed the most errors during an emergency simulation and highlighted the necessity to include this member in the training procedures for robotic surgery. Hertz P. et al,18 in their study of robotic surgery training programs, state that assistant surgeons should be given basic training in robotic surgery before participating in these surgeries, particularly due to their rotation within surgical teams.Concerning the surgical instrument technician and the nurse, it was observed that although essential members of the robotic surgery team, their actions did not interfere in the outcome of the emergency uncoupling of the robotic system. They were therefore considered as non-critical elements in these situations, especially when the teamwork is effective and adequately coordinated.In the present study, from the first to second simulation, the GI group showed improvement in their technical and non-technical skills, and in the time spent to decouple the robotic system from the patient.…”
mentioning
confidence: 99%
“…4,[28][29][30][31][32] Robotic-assisted surgery surgeons report that essential skills for team members include troubleshooting and handling errors, knowledge of and the handling of robotic instruments, effective communication, and understanding the roles of other team members. 33 Our preliminary observations of data collected during 65 RAS procedures across 4 hospitals 34 demonstrated challenges associated with docking the robot, 35 managing the surgical environment, 36 and teamwork (communication and coordination). Operational concerns were expressed among OR staff leaders about implementing an "efficiency-focused" intervention given the high rates of staff turnover, burnout, and low morale as a result of the COVID-19 pandemic.…”
mentioning
confidence: 92%
“…The introduction of robots into the operating room (OR) in particular has introduced a range of new challenges that teams need to account for including (1) a greater need to negotiate the physical environment, (2) adoption of team communication to manage various tasks and technologies, and (3) management of the robotic system to optimize efficiency and workflow 4,28–32 . Robotic-assisted surgery surgeons report that essential skills for team members include troubleshooting and handling errors, knowledge of and the handling of robotic instruments, effective communication, and understanding the roles of other team members 33 . Our preliminary observations of data collected during 65 RAS procedures across 4 hospitals 34 demonstrated challenges associated with docking the robot, 35 managing the surgical environment, 36 and teamwork (communication and coordination).…”
mentioning
confidence: 99%
“…New curricula must incorporate virtual reality and simulation training to achieve competency across basic skills prior to progressing to in vivo operating [1,2]. These curricula have previously enabled validation of simulation-based training in robotic surgery, with consensus opinion supporting this approach [3][4][5]. Despite the availability of multiple virtual reality simulators for robotic training [6], currently only the DaVinci Skills ® Simulator™ and the dV-Trainer ® have face, content, construct, concurrent and predictive validity [7] and Da Vinci technology currently dominates robotic education and training.…”
Section: Introductionmentioning
confidence: 99%